PENYULUHAN HAK DAN KEWAJIBAN ISTRI DALAM RUMAH TANGGA BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI DESA RANTAU MINYAK - Putri, Rizky Silvia; Mulyani, Wike (Jurnal GeoCivic, 2024)
Counselling on the rights and obligations of wives in the household based on Law Number 1 of 1974 in Rantau Minyak Village aims to explain and understand the rights and obligations of wives in the context of the household based on Law Number 1 of 1974 on Marriage. This research was conducted in Rantau Minyak Village using qualitative methods, involving interviews, observation, and documentation. This counselling will discuss the purpose of marriage, the legal requirements of marriage, and the rights and obligations of wives in carrying out their role as housewives. In addition, this research will also highlight the reality of wives' lives in the village, especially in terms of equal rights and responsibilities of wives in supporting a harmonious and happy family life, as well as how Law Number 1 of 1974 affects and provides the rights and obligations of wives in maintaining a happy and lasting family. The results of this study are expected to contribute to a deeper understanding of the rights and obligations of wives in the context of marriage law in Indonesia.